The Chest Radiographic Thoracic Area Can Serve as a Prediction Marker for Morbidity and Mortality in Infants With Congenital Diaphragmatic Hernia - Weis, Meike; Burhany, Sosan; Perez Ortiz, Alba; Nowak, Oliver; Hetjens, Svetlana; Zahn, Katrin; Schoenberg, Stefan; Schaible, Thomas; Rafat, Neysan (Frontiers in Pediatrics, 2021)
Objective: Valid postnatal prediction parameters for neonates with congenital diaphragmatic hernia are lacking, but recently the chest radiographic thoracic area was proposed to predict survival with high sensitivity. Here, we evaluated whether the chest radiographic thoracic area correlated with morbidity and mortality in neonates with congenital diaphragmatic hernia and was able to predict these with higher sensitivity and specificity than prenatal observed-to-expected lung-to-head ratio. Methods: In this retrospective cohort study all neonates with congenital diaphragmatic hernia admitted to our institution between 2013 until 2019 were included. The chest radiographic thoracic area was measured using the software Horos (V. 3.3.5) and compared to observed-to-expected (O/E) lung-to-head ratio (LHR) diagnosed by fetal ultrasonography in relation to outcome parameters including survival, extracorporeal membrane oxygenation support and chronic lung disease. Results: In this study 255 neonates were included with a survival to discharge of 84%, ECMO support in 46% and 56% developing a chronic lung disease. Multiple regression analysis demonstrated that the chest radiographic thoracic area correlates significantly with survival (p = 0.001), ECMO support (p < 0.0001) and development of chronic lung disease (p = 0.0193). The chest radiographic thoracic area displayed a higher prognostic validity for survival (AUC = 0.822), ECMO support (AUC = 0.802) and developing a chronic lung disease (AUC = 0.855) compared to the observed-to-expected lung-to-head ratio. Conclusions: Our data suggest that the postnatal chest radiographic thoracic area might be a better prognostic parameter for morbidity and mortality than the prenatal observed-to-expected lung-to head ratio.